UroLift: a new minimally-invasive treatment for benign prostatic hyperplasia. (December 2016) - Jones, Patrick; Rai, Bhavan P.; Aboumarzouk, Omar; Somani, Bhaskar K.
'UroLift' has emerged as a new minimally-invasive nonablative surgical technique for benign prostatic hyperplasia (BPH). We discuss the procedure, cost, evidence, advantages and disadvantages of this procedure. It is a novel technology suitable for a selected group of patients that allows for a bespoke treatment for men with BPH.